1999
DOI: 10.1046/j.1365-2567.1999.00925.x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of activation induced cell death in human T blasts despite CD95L
up‐regulation: protection from apoptosis by MEK signalling

Abstract: SUMMARYThe generation of effective immunity requires that antigen-speci®c T cells are activated, clonally expanded and ultimately eliminated by apoptosis. The involvement of CD95-mediated apoptosis in T-cell elimination is well established, but the conditions which regulate the death pathway under normal circumstances are still emerging. Using superantigen-activated human T cells, we found that whilst T-cell receptor (TCR) signalling triggered up-regulation of CD95 ligand (CD95L), the majority of T cells were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Most of these early studies, however, were done in T cell lines or T cell clones and not in human primary T cells (32-35). Interestingly, T cells have been shown to also die in a DR-independent and caspase independent manner (36-38). Towards understanding the mechanism of epitope specific AICD in CD8+ human primary CTL, we have also recently shown that the AICD in human melanoma associated antigen specific CD8+ primary CTL is a JNK activation driven, DR-independent, caspase-independent, mitochondria-centric process (10, 13, 14).…”
Section: Discussionmentioning
confidence: 99%
“…Most of these early studies, however, were done in T cell lines or T cell clones and not in human primary T cells (32-35). Interestingly, T cells have been shown to also die in a DR-independent and caspase independent manner (36-38). Towards understanding the mechanism of epitope specific AICD in CD8+ human primary CTL, we have also recently shown that the AICD in human melanoma associated antigen specific CD8+ primary CTL is a JNK activation driven, DR-independent, caspase-independent, mitochondria-centric process (10, 13, 14).…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore likely that ERK-dependent apoptosis in these cells does not require the mitochondrial amplification loop and thus would not be sensitive to an inhibition of the mitochondrial pathway. Nevertheless, ERK activation has been shown to prevent Fas-and TRAIL-mediated apoptosis in Jurkat T cells [48][49][50] and in 3T3 fibroblasts ectopically expressing Fas. 51 In Jurkat cells, however, ERK did not affect caspase 8 cleavage at the level of the DISC but rather prevented downstream cleavage of Bid and the onset of mitochondrial amplification by caspase 9.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the cells were washed once in PBS with 1% bovine serum albumin and analyzed quantitatively for fluorescein isothiocyanate incorporation using a Becton-Dickinson FACSCalibur flow cytometer and data analyzed using CellQuest software. TUNEL-positive staining was established by setting a gate at the highest staining 5% of the population of untreated cells as previously outlined (25).…”
Section: Methodsmentioning
confidence: 99%